2015
DOI: 10.1093/jac/dku568
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Escherichia coli NDM isolates with decreased susceptibility to aztreonam/avibactam: role of a novel insertion in PBP3

Abstract: The acquisition of β-lactamases is the predominant mechanism of β-lactam resistance in Enterobacteriaceae. We have demonstrated that small PBP3 changes will affect the susceptibility to a broad range of β-lactams. These changes were identified in multiple MLST lineages of E. coli, and were enriched in NDM-containing isolates. However, they were not present in other key species of Enterobacteriaceae despite significant conservation among the PBP3 proteins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
118
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(125 citation statements)
references
References 32 publications
5
118
0
2
Order By: Relevance
“…For 16 isolates, the mechanism(s) appears to be aztreonam related rather than avibactam related, because those isolates remained susceptible to ceftazidime-avibactam. It is possible that some of the isolates may harbor mutations in PBP3, such as the 4-amino-acid insertion shown to reduce the activity of aztreonam-avibactam (28). Resistance may also arise from single amino acid substitutions or ⍀-loop mutations in coresident class A and C serine ␤-lactamases that can lead to a reduced affinity of avibactam for the ␤-lactamase binding site, resulting in poor inhibition of ␤-lactamase activity (13,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…For 16 isolates, the mechanism(s) appears to be aztreonam related rather than avibactam related, because those isolates remained susceptible to ceftazidime-avibactam. It is possible that some of the isolates may harbor mutations in PBP3, such as the 4-amino-acid insertion shown to reduce the activity of aztreonam-avibactam (28). Resistance may also arise from single amino acid substitutions or ⍀-loop mutations in coresident class A and C serine ␤-lactamases that can lead to a reduced affinity of avibactam for the ␤-lactamase binding site, resulting in poor inhibition of ␤-lactamase activity (13,29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, spread of CPE could be the tipping point when substantial morbidity and mortality from antibiotic resistance comes to the fore. 1 Few alternative antibiotics (eg, colistin, fosfomycin, and tigecycline) remain, 2 and although resistance can extend even to agents still in development or recently approved, 3,4 public health eff orts are beginning to emphasise containment of CPE in populations and health-care networks. This requires an understanding of the geographical distribution of CPE infections, their population reservoirs, and the risk factors for acquisition.…”
Section: Introductionmentioning
confidence: 99%
“…Studies confirmed that mobile-resistance elements, such as plasmids, transposons (Tn) and insertion sequences (IS), are responsible for the distribution of this superresistant gene, and they are regarded as major mechanisms driving the dramatically increased prevalence of carbapenem-resistant Enterobacteriaceae isolates (3)(4)(5).…”
mentioning
confidence: 99%
“…Additional bla NDM-1 plasmids ranging from 40 kb to 400 kb in size have been fully sequenced and documented for their effective transferability within species (3)(4)(5). Recent surveys demonstrated the large similarities of the genetic structures surrounding the bla NDM-1 gene among different members of the Enterobacteriaceae family, which further highlights the potential for the extensive spread of this determinant of resistance.…”
mentioning
confidence: 99%